Bonhoeffer's theological formation Berlin, Barth, and Protestant theology - DeJonge, Michael P. 1978- (Oxford Oxford University Press, 2012)
An examination of the academic formation of Dietrich Bonhoeffer's theology, arguing that the young Bonhoeffer reinterpreted for a modern intellectual context the Lutheran understanding of the 'person' of Jesus Christ and distinguishing his theology from that of contemporaries Karl Barth and Karl Holl.
Keywords: Philosophical Theology; Bonhoeffer, Dietrich, 1906-1945; Bonhoeffer, Dietrich, 1906-1945--Childhood and youth; Philosophical theology